1901 Id. Sess. Laws 117, 120, § 37 pt. 15 - (:unkn) unknown (General Publisher, 1901)
Amended the Boise city charter to authorize the regulation of storage and sale of gunpowder, dynamite, giant powder, nitro-glycerine, oil, and other combustible material. Also allowed the city to prevent the manufacture in the city, and to "prevent by all possible and proper means" the danger or risks of injury or damage by fire from carelessness, negligence, or otherwise.
--
Keywords: TRANSFER; MANUFACTURE & STORAGE OF GUNPOWDER